Uncovering the ‘Hyper’ Signs Mechanism of the Khong Guan Meme as an Object of Simulacrum Design through a Hypersemiotic Approach - Elvira Yesica Ginting (Institut Seni Indonesia Denpasar, 2021)
Cyberspace is no longer a stutter for the masses of consumers who are addicted to memes. It is no longer a confusion between what is reality and what is hyperreality for them. Meme is a digital design object that was born from the development of cyber power and has a message content in fulfilling the purpose of communicating, interacting socially through social media or social networks and digital culture. The message is composed of a network of signs that have a mechanism in it to produce meaning. Today, many memes have gone viral among the consumer masses, one of which is the meme Khong Guan biscuit. However, the phenomenon of the ‘hyper’ signs mechanism has not yet been written scientifically by researchers. In fact, the meme Khong Guan has a network of ‘hyper’ signs which from the beginning until now has moved dynamically and has succeeded in stealing the spotlight of the masses of Indonesian consumers. Therefore, hypersemiotics as a theory of ‘hyper’ signs and the results of criticism of conventional semiotics (especially structural semiotics which is closely related to structuralism) can be used as an approach to find out the movement of the ‘hyper’ sign elements in Khong Guan meme which is engaged in finding new codes and generate dynamic meaning.